Total cholesterol and HDL cholestrol as risk factor of prediabetes and diabetes in palembang city - Gresi Elyantari; Suryadi Tjekyan; Novrikasari Novrikasari; Zulkarnain Zulkarnain; Rostika Flora; Ngudiantoro Ngudiantoro; Mariana Mariana (Jurnal Kebidanan dan Keperawatan Aisyiyah, 2018)
This study aims to determining the incidence of prediabetes and diabetes with total cholesterol and HDL as risk factor for the incidence of prediabetes and diabetes in the Palembang city. The research design was used by crossectional with 329 respondent, data was conducted by home visit and biomedical measurement of blood sugar and total cholesterol. The data were analyzed using chi-square. The results of the study showed that the incidence of pre-diabetes 19,8% and the incidence of diabetes14%. There was a significant relationship between total cholesterol and the incidence of prediabetes(p value= 0.003) and diabetes (0,137). the increasing of total cholesterol levels can be an early predictor of pancreatic β cell dysfunction. Prediabetes can increase the absolute risk to diabetes. by knowing lipid profile as risk factor of pre-diabetes, early prevention program can be conducted to decrease the diabetes incidence.